Preparation of Pickering Emulsions Stabilized by Modified Silica Nanoparticles via the Taguchi Approach - Fatemeh Heidari; Seid Mahdi Jafari; Aman Mohammad Ziaiifar; Nicolas Anton (MDPI AG, 2022)
In this study, oil-in-water Pickering emulsions (PEs) were prepared by modified silica nanoparticles (MSNs) with cetyltrimethylammonium bromide (CTAB) using the Taguchi approach. The surface modification of SiO2 nanoparticles (NPs) was performed in different conditions, temperatures, pH levels, and amounts of CTAB as a coating agent, followed by an evaluation of their physicochemical properties. After treatment of the SiO2 NPs, the relationship of the MSNs' surface properties and their efficiency in stabilizing Pickering emulsions was investigated by considering the zeta potential (ZP) and emulsion physical stability as main responses, respectively. Results disclosed were then supported by additional characterization, such as thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, contact angle (CA), and scanning electron microscopy. Results demonstrated that temperature has the most important role in the treatment of SiO2 nanoparticles, and allows for the identification of the best experimental conditions, i.e., range of zeta potential of MSNs to produce more efficient NPs, as well as the best stabilization of PEs.